2014
DOI: 10.1007/s00436-014-4052-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and synthesis of silver nanoparticles using Isaria fumosorosea against human vector mosquitoes

Abstract: The efficacy of silver generated larvicide with the help of entomopathogenic fungi, Isaria fumosorosea (Ifr) against major vector mosquitoes Culex quinquefasciatus and Aedes aegypti. The Ifr-silver nanoparticles (AgNPs) were characterized structurally and functionally using UV-visible spectrophotometer followed by scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy and Fourier transform infrared (FTIR) spectra. The optimum pH (alkaline), temperature (30 °C) and agitation (150 rpm) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 31 publications
10
36
0
Order By: Relevance
“…Furthermore, the appearance of a characteristic band around 470 µm during the UV‐spectroscopic characterization of filtrate also confirmed the formation of nanoparticles. Our results can be correlated to the findings of Banu and Balasubramanian, Mukherjee et al and Amersan et al , who have all reported similar synthesis of metal‐entomopathogenic fungi nanoparticles. The change in colour of filtrate during the biosynthesis of nanoparticles can be attributed to the following: (i) the excitation of surface plasmon vibration of nanopraticles and (ii) bio‐reduction of metals related to the metabolic utilization of nitrate through reduction of nitrate and ammonia .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, the appearance of a characteristic band around 470 µm during the UV‐spectroscopic characterization of filtrate also confirmed the formation of nanoparticles. Our results can be correlated to the findings of Banu and Balasubramanian, Mukherjee et al and Amersan et al , who have all reported similar synthesis of metal‐entomopathogenic fungi nanoparticles. The change in colour of filtrate during the biosynthesis of nanoparticles can be attributed to the following: (i) the excitation of surface plasmon vibration of nanopraticles and (ii) bio‐reduction of metals related to the metabolic utilization of nitrate through reduction of nitrate and ammonia .…”
Section: Discussionsupporting
confidence: 90%
“…For SEM, fungal nanoparticles were processed by using the methods of Banu and Balasubramanian and Amersan et al The nanoparticles produced were washed three times with 0.1 M potassium phosphate buffer (pH = 7.2). The material was then fixed with 2.5% glutaraldehyde in PBS buffer for 3 h at 4 °C then rinsed twice with PBS for 10 min each time followed by rinsing with ddH 2 O.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations